A Brief Review on the In Situ Synthesis of Boron-Doped Diamond Thin Films - Vadali V. S. S. Srikanth; P. Sampath Kumar; Vijay Bhooshan Kumar (International Journal of Electrochemistry)
Diamond thin films are well known for their unsurpassed physical and chemical properties. In the recent past, research interests in the synthesis of conductive diamond thin films, especially the boron-doped diamond (BDD) thin films, have risen up to cater to the requirements of electronic, biosensoric, and electrochemical applications. BDD thin films are obtained by substituting some of the sp3 hybridized carbon atoms in the diamond lattice with boron atoms. Depending on diamond thin film synthesis conditions, boron doping routes, and further processing steps (if any), different types of BDD diamond thin films with application-specific properties can be obtained. This paper will review several important advances in the synthesis of boron-doped diamond thin films, especially those synthesized via gas phase manipulation.